A xCT role in tumour-associated ferroptosis shed light on novel therapeutic options - Daniela Criscuolo; Francesco Morra; Angela Celetti (Open Exploration Publishing Inc., 2022)
Solute carrier family 7 member 11 (SLC7A11; also known as xCT), a key component of the cystine/glutamate antiporter, is essential for the maintenance of cellular redox status and the regulation of tumor-associated ferroptosis. Accumulating evidence has demonstrated that xCT overexpression, resulting from different oncogenic and tumor suppressor signaling, promotes tumor progression and multidrug resistance partially via suppressing ferroptosis. In addition, recent studies have highlighted the role of xCT in regulating the metabolic flexibility in cancer cells. In this review, the xCT activities in intracellular redox balance and in ferroptotic cell death have been summarized. Moreover, the role of xCT in promoting tumor development, drug resistance, and nutrient dependency in cancer cells has been explored. Finally, different therapeutic strategies, xCT-based, for anti-cancer treatments have been discussed.